2012
DOI: 10.1597/10-035
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Delivery System of Probiotic Drop and Its Effect on Dental Caries Risk Factors in Cleft Lip/Palate Children

Abstract: The novel drop containing L. reuteri may not reduce the levels of salivary mutans streptococci and lactobacilli in cleft lip/palate children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 32 publications
0
18
1
1
Order By: Relevance
“…This may partly explain the discrepancy between our current results and those of earlier studies. Recently, a study by Cildir et al demonstrated that one daily dose of L. reuteri fails to reduce the salivary MS counts in children [23]. More research is clearly needed on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…This may partly explain the discrepancy between our current results and those of earlier studies. Recently, a study by Cildir et al demonstrated that one daily dose of L. reuteri fails to reduce the salivary MS counts in children [23]. More research is clearly needed on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…This inconsistency may be due to the numerous strains investigated or differences in study design and/or study population [Näse et al, 2002;Cildir et al, 2009;Stecksén-Blicks et al, 2009;Lexner et al, 2010;Jindal et al, 2011;Singh et al, 2011;Cildir et al, 2012]. Certain naturally occurring LBC inhibit the growth of a patient's autologous MS in vitro.…”
mentioning
confidence: 99%
“…[256719] However, some other studies have not shown any difference in SM counts. [8121320] Several studies have shown a relationship between dental caries and SM counts. [21] It is very difficult to compare the results of studies because of different study designs, duration of intervention, the parameters evaluated, and the type of probiotics used, combination of different species, and their vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…[891011] Two studies have been carried out with the use of drops containing Lactobacillus reuteri and no differences have been observed between salivary counts of Lactobacillus (LB) and SM. [1213] Regarding the conflicting results of previous studies about the effects of probiotic products on oral health and as well as the importance of oral health, this study was performed. [14]…”
Section: Introductionmentioning
confidence: 99%